2016
DOI: 10.1080/07391102.2015.1135823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low urea concentrations on protein-water interactions

Abstract: Solvent properties of aqueous media (dipolarity/polarizability, hydrogen bond donor acidity, and hydrogen bond acceptor basicity) were measured in the coexisting phases of Dextran-PEG aqueous two-phase systems (ATPSs) containing .5 and 2.0 M urea. The differences between the electrostatic and hydrophobic properties of the phases in the ATPSs were quantified by analysis of partitioning of the homologous series of sodium salts of dinitrophenylated amino acids with aliphatic alkyl side chains. Furthermore, partit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…VNAR showed resistance not only to low temperature but also to 1 M urea (Figure 3f). In this study, 0.5 M urea exhibits protein denaturing effects [32]. It has also been reported that a high concentration of urea inhibits antigen-antibody reactions [33].…”
Section: Discussionsupporting
confidence: 59%
“…VNAR showed resistance not only to low temperature but also to 1 M urea (Figure 3f). In this study, 0.5 M urea exhibits protein denaturing effects [32]. It has also been reported that a high concentration of urea inhibits antigen-antibody reactions [33].…”
Section: Discussionsupporting
confidence: 59%
“…We observed more complex dependence of sfGFP stability and refolding on the presence of crowding agents. In fact, our previous data of the analysis of the urea-induced unfolding of structurally-different globular proteins [33,34], and the results of this study allow the conclusion that even in the absence of direct interaction between a crowding agent and the target protein the excluded volume theory cannot always be used to explain the experimental data. In fact, we show here that all crowding agents used in this study do not affect the structure of sfGFP.…”
Section: Discussionmentioning
confidence: 76%
“…This hypothesis is supported by the observed increase in the degree of sfGFP aggregation during the protein unfolding-refolding processes with the increase in the molecular mass and concentration of PEGs. In fact, it is evident now that the behavior of biomolecules in the conditions of macromolecular crowding cannot be explained only within the frames of the excluded volume effects and/or direct interaction between tested biomolecules and crowding agents [28,29,33,34]. The changes in the sfGFP stability towards the GTC action and the capability of this protein to refold in the presence of different crowding agents are shown here to be dependent on the type and concentration of the polymer used as a crowding agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations